Differential performance evaluation of feedbacks effectiveness in analog circuitry - V. L. Svirid (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It was offered to evaluate the performance efficiency of negative feedbacks using the differential method of analog circuitry analysis, which was developed by author. This method allows to take into account the features of measurement process during the experimental test of this efficiency on the given model and to get results that are more reliable, agreed to the theoretical intelligence.